Semi-quantitative determination of ion transfers at an interface between water and quaternary ammonium polybromide droplets through stochastic electrochemical analysis. (1st May 2018) - Lee, Semi; Park, Sangeun; Kim, Kyung Mi; Chang, Jinho
Abstract: In this article, we present stochastic electrochemical analyses for the semi-quantitative determination of ion transfers (ITs) at an interface between water and electrochemically generated quaternary ammonium polybromide (QBr2n+1 ) droplets (water|QBr2n+1 ) in QBr aqueous solutions containing different acids (HAs). The concentration of Br − in QBr2n+1, C B r − ( Q B r 2 n + 1 ) is linearly proportional to C A − ( a q ) with the proportionality constant, which was estimated from the difference between the two partition coefficients of H + and A − from water toward QBr2n+1, K H + − K A −, and the ratio of the mean activity coefficient of the aqueous over that of the QBr2n+1 phase, γ ±, a q / γ ±, Q B r 2 n + 1 . C B r − ( Q B r 2 n + 1 ) also shows the linear function of C Q + ( a q ) with ( γ ±, a q / γ ±, Q B r 2 n + 1 ) K Q + as its proportionality constant. The stochastic chronoamperometric analyses of QBr2n+1 droplets during their particle-impacts on Pt UME in acidic solutions containing either N -methyl- N -ethyl pyrrolidinium bromide (MEPBr) or ethylpyridinium bromide (EPyBr) as model QBrs can provide indirect information about C B r − ( Q B r 2 n + 1 ), and we estimated the relative order to be K C + ( L i + o r N a + ), K H +, and K A − : K C + ( L i + o r N a + ) < K H + < K A −, where K H S O 4 − < K C l O 4 − < K C l − in K A − and K N a + < K L i + in K C + . Also, we found that Br − -IT at water|QBr2n+1 is effectively limited by A − -IT in the acidic solutions, and Cl − is most significantly transferred to QBr2n+1, leading to the complete inhibition of Br − -IT into QBr2n+1 . Graphical abstract: